2022
DOI: 10.1002/jcsm.13124
|View full text |Cite
|
Sign up to set email alerts
|

Loss of FoxOs in muscle increases strength and mitochondrial function during aging

Abstract: Background Muscle mitochondrial decline is associated with aging‐related muscle weakness and insulin resistance. FoxO transcription factors are targets of insulin action and deletion of FoxOs improves mitochondrial function in diabetes. However, disruptions in proteostasis and autophagy are hallmarks of aging and the effect of chronic inhibition of FoxOs in aged muscle is unknown. This study investigated the role of FoxOs in regulating muscle strength and mitochondrial function with age. Methods We measured mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Among the 10 activated pathways, previous studies have shown that JAK2/STAT3 could activate the FOXO signaling pathway (43–45), and JAK2/STAT3 could be activated via RAGE (46). In addition, the FOXO signaling pathway has been proved to induce muscle atrophy in previous studies (47,48). In the study, we also proved that the expression of RAGE was significantly associated with the expression of SAA ( P = 0.0089, R = 0.54, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Among the 10 activated pathways, previous studies have shown that JAK2/STAT3 could activate the FOXO signaling pathway (43–45), and JAK2/STAT3 could be activated via RAGE (46). In addition, the FOXO signaling pathway has been proved to induce muscle atrophy in previous studies (47,48). In the study, we also proved that the expression of RAGE was significantly associated with the expression of SAA ( P = 0.0089, R = 0.54, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, we further found that the FOXO signaling pathway was significantly activated and ranked within top 10 signaling pathway. FOXO signaling pathway has been found to be relevant to muscle atrophy in other studies (47,48). Sandri et al (47) found that the activity of the PI3K/AKT pathway decreases, leading to activation of FOXO transcription factors and atrogin-1 induction.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Once insulin binds to the insulin receptor, it can activate the phosphoinositide 3-kinase (PI3K)/Akt/mTOR pathway, stimulating protein synthesis [ 49 ]. Moreover, activation of the PI3K/Akt pathway inhibits Foxo, which suppresses the transcription of target atrophic genes and protein degradation [ 50 ]. In the current study, gene expression of Akt and mTOR was not affected by KD feeding; however, increased Foxo1 expression in DM was reduced by KD feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of mitochondrial proteostasis leading to the progressive loss of cellular function is one of the hallmarks of aging [77]. Exercise is an effective means of slowing down aging and is effective in preventing or delaying many diseases caused by imbalances in mitochondrial proteostasis [78].…”
Section: Exercise and Mitochondrial Proteostasismentioning
confidence: 99%